Desenvolvimento e análise de passivação com dióxido de titânio em células solares com campo retrodifusor seletivo - Model, José Cristiano Mengue (2017)
The surface passivation is an important step in solar cell manufacturing since it intends to fix the surface defects. In order to develop p-type crystalline silicon solar cells, solar grade, with surface passivation provided by titanium dioxide film, atmospheric pressure chemical vapor deposition (APCVD) and electron beam deposition (E-Beam) were carried out. For the films deposited by E-Beam, the thickness of TiO2, which has produced the most efficient solar cell, was of 80 nm. It was observed that how thicker the film, higher was the internal quantum efficiency (IQE) for short wavelengths, indicating a surface passivation that changes according to the thickness. The cells in which the film deposition on the front face was performed by APCVD were as efficient in to reduce the reflection as those with films deposited by E-Beam, although the first technique did not produce films with high homogeneity with regard to thickness. When the both techniques to deposit films on the back surface were compared, it was observed that the better results were obtained with APCVD films. Regarding the thickness of the films obtained by APCVD, it was not observed difference between the electrical characteristics of solar cells with thin and thick films. The most efficient solar cell produced in this work used TiO2 films obtained by chemical vapor deposition on both sides, reaching the efficiency of 15.6% and short-circuit current density of 34.9 mA/cm².